Tools design to support accessibility testing on mobile applications (2020)
Mobile applications have become a must-have in everyday life and their development is always improving as new methods and tools do to allow a better user experience. During the development of an app, the developers must ensure different quality attributes and one of these attributes is accessibility. However, this quality attribute is mostly ignored during development and requires a big effort to test it. The purpose of this paper is to develop a tool implementing an Android accessibility service, that will supports developers during the development of an app, show tips to make an app more accessible by developing an app, and why it is so important to make applications more accessible